Comparative Study of the Outcome of Facial Laceration Repaired by Vicryl Rapide versus Prolene - Mahmood, Farman; Ullah, Asmat; Choudhary, Shahid Hameed; Alam, Khurshid; Ghani, Umar Fayyaz; Nasir, Muhammad Ali (Pakistan Armed Forces Medical Journal, 2025)
Objective: To study the efficacy of Vicryl Rapide versus Prolene in patients with facial lacerations in terms of cosmetic outcomes and complications. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Plastic Surgery, Combined Military Hospital, Rawalpindi, Pakistan Jul 2020 to Jun 2022. Methodology: A total of 266 patients with facial lacerations were included in our study. Patients were divided into two Groups; one received Vicryl Rapide, while the second received Prolene. Patients were photographed at baseline and ten days post-suturing. Patients were photographed at three- and six-months for comparison of local inflammation and stitch scarring, which were calculated on a scoring system. Results: The sample was composed of 65.8% males, with a mean age of 35.09±9.32 years. There was no difference between the two Groups with regard to pre-procedure characteristics. Inflammation scores at baseline, at three and six months, were not significantly different (p=0.766, p=0.374, and p=0.854, respectively). Similarly, scarring scores at baseline, at three and six months, were also not significantly different (p=0.066, p=0.733, and p=0.416, respectively). The total complication rate of the study was 9.4% (n=25), while complications were lower with Vicryl Rapide; the difference did not achieve statistical significance (p=0.141). Infection was the most common complication seen: 13(4.9%), followed by wound dehiscence and train tracking, with frequencies of 7(2.7%) and 6(2.3%), respectively. Differences between individual complications did not achieve statistical significance either (p=0.155, p=0.055, and p=0.409, respectively). Conclusion: Vicryl Rapide sutures have similar outcomes in cosmesis and complications to Prolene.